EFFECT OF BACK EXTENSORS ENDURANCE EXERCISES ON PHYSIOLOGICAL AND PSYCHOSOCIAL VARIABLES IN PATIENTS WITH LONG-TERM MECHANICAL LOW-BACK PAIN
Management of Long-Term Mechanical Low-Back Pain (LMLBP) poses a challenge to clinicians. McKenzie Protocol (MP) is a common efficacious conservative therapy but its use in addressing back muscles inhibition accompanying LMLBP is doubtful. However, back endurance exercise is suggested to enhance muscle reactivation. This study was designed to investigate the effect of static or dynamic back extensors endurance exercise in combination with MP on physiological and psychosocial variables in patients with LMLBP. Eighty four consecutive patients with LMLBP were recruited from the physiotherapy department of Obafemi Awolowo University Teaching Hospitals-Complex, Ile-Ife. They were randomly assigned to one of three treatment groups; the MP Group (MPG) (n=29), MP plus Static Back Endurance Exercise Group (MPSBEEG) (n=27) and MP plus Dynamic Back Endurance Exercise Group (MPDBEEG) (n=28). MP involved standardized extension exercises, static exercise involved 10-seconds (sec) static-hold in five exercise progression positions in prone-lying while dynamic exercise was a 10-repetition (rep) variant of static exercise. At baseline, physiological and psychosocial variables were measured. Treatment was given thrice weekly for eight weeks and outcomes were assessed at the end of 4th and 8th week. Physiological variables namely pain intensity, muscle fatigue, static and dynamic endurance were measured using quadruple visual analogue scale, Borg Scale (BS), Biering-Sorensen Test (BST) and Repetitive Arch-Up Test (RAUT) respectively. Psychosocial variables measured were activity limitation, disability, fear-avoidance behaviour, and pain self-efficacy belief using Roland-Morris Back Pain Questionnaire (RMBPQ), Oswestry low-back disability questionnaire, fear-avoidance beliefs questionnaire, and Pain Self-Efficacy Questionnaire (PSEQ) respectively. Data were analyzed using mean, ANOVA, Kruskal-Wallis and post-hoc tests at p=0.05. A drop-out rate of 20.2% was observed in the study. Twenty five, 22 and 20 participants in MPG, MPSBEEG and MPDBEEG respectively whose ages range between 38 and 62 years completed the study. Within-group comparison across the 3 time-points of the study showed significant differences in the physiological and psychosocial variables in MPG, MPSBEEG and MPDBEEG. There were significant differences in groups mean change scores on BST (14.6'8.44, 45.7'17.0 and 17.1'10.2 sec), RAUT (2.88'1.88, 12.9'11.1 and 10.7'6.51 rep), BS (12.6'2.16, 10.1'2.08 and 10.8'2.19), RMBPQ (3.36'0.76, 3.72'0.70 and 4.20'0.52) and mean rank score on PSEQ (26.6, 36.5 and 40.5) at week 4. Also, significant differences were observed in BST (29.6'8.44, 60.7'17.1 and 32.1'10.2 sec), RAUT (8.36'2.22, 18.1'10.1 and 16.6'6.24 reps), BS (3.88'1.67, 5.41'2.32 and 4.35'1.63) and mean rank score on PSEQ (23.5, 37.4 and 43.5) at week 8. Post-hoc test showed that MPSBEEG had significantly higher mean change in BST, RAUT and BS scores at week 4 and 8 respectively. The MPDBEEG had higher mean change in RMBPQ and PSEQ at week 4, and in PSEQ at week 8. Combining static back endurance exercise with Mckenzie protocol led to higher improvement in physiological variables of muscle endurance and reduction in fatigue while the addition of dynamic back endurance exercise resulted in higher improvement in psychosocial variables of activity limitation and pain self-efficacy. Combining static and dynamic back endurance exercise with Mckenzie protocol may be recommended in improving physiological and psychosocial variables in patients with LMLBP.